Changing conversations in primary care for patients living with chronic conditions: pilot and feasibility study of the ICAN Discussion Aid - Claudia C Dobler; Víctor M Montori; Kasey R Boehmer; Anjali Thota; Megan Branda; Rachel Giblon; Emma Behnken; Paige Organick; Summer V Allen; Kevin Shaw (BMJ Open)
Purpose To pilot test the impact of the ICAN Discussion Aid on clinical encounters.Methods A pre–post study involving 11 clinicians and 100 patients was conducted at two primary care clinics within a single health system in the Midwest. The study examined clinicians’ perceptions about ICAN feasibility, patients’ and clinicians’ perceptions about encounter success, videographic differences in encounter topics, and medication adherence 6 months after an ICAN encounter.Results 39/40 control encounters and 45/60 ICAN encounters yielded usable data. Clinicians reported ICAN use was feasible. In ICAN encounters, patients discussed diet, being active and taking medications more. Clinicians scored themselves poorer regarding visit success than their patients scored them; this effect was more pronounced in ICAN encounters. ICAN did not improve 6-month medication adherence or lengthen visits.Conclusion This pilot study suggests that using ICAN in primary care is feasible, efficient and capable of modifying conversations. With lessons learned in this pilot, we are conducting a randomised trial of ICAN versus usual care in diverse clinical settings.Trial registration number NCT02390570.